(3QSGdI aj TQM eYfi GdJHYjVjIs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hGdUdGI Ydi fHjg EYde Cf GdHYVjI MjK bGd ai TQM GdcGajI hJYQagG Ci ef GdHjGfI HCf jchf bHd ef Ch HYOgG s
(3BNQgG (B:s
(3de jLF GdNWGH ddcaQI Ydi GdYehe abO LGA cPdc ceG ai bhdg JYGdi ai ShQI GdGfaGd bd ddPjf caQhG Cf jfJghG jZaQ dge eG bO Sda Gf Gddg jZaQ Cf jTQc Hg hGdJYdjd Hbhdg JYGdi Efg gh GdZahQ GdQMje GdMeO ddg Ydi GdJeGe s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdJGSYIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9237) s
Keywords: (3GdJhMjO hGdedd hGdfMds